DAMPAK PENGALAMAN KERJA DAN TINGKAT PENDIDIKAN PADA KINERJA PERANGKAT DESA DI KECAMATAN BANDUNGAN KABUPATEN SEMARANG - Aba Yayit Al Bustomi,; Yuniarto Rahmat Satato,; Enik Rahayu, (Journal of Innovation Research and Knowledge, 2025)
This study aims to determine how the performance of village officials in Bandungan District, Semarang Regency, is impacted by their work experience. to ascertain the impact of village leaders' educational attainment on their effectiveness. to ascertain how the training and work experience of village administrators impact their performance. to determine which factors most affect the village authorities' performance metrics. By creating a questionnaire for respondents (village authorities), who will respond to it, a quantitative, factual, and the right research approach is used. 88 municipal authorities took part in this survey. The results of the study suggest that job experience and educational achievement may influence one another or both. Higher education and more work experience are associated with improved performance for village authorities. It is clear that the education level variable has the most influence on the performance variable